2021
DOI: 10.22454/fammed.2021.267781
|View full text |Cite
|
Sign up to set email alerts
|

Resident Outcomes and Perspectives Over 2 Years of a New Scholarship Curriculum

Abstract: Background and Objectives: Scholarship is recognized as a challenge in many family medicine residency programs. Among evaluations of scholarship curricula, few describe resident experiences of such interventions. To bridge this gap in knowledge, we measured resident confidence, satisfaction, and participation before and after implementing a new scholarship curriculum. Methods: The redesigned curriculum included a structured project timeline, resident research in progress meetings, faculty mentorship, scholarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These include longitudinal research curricula spanning the entirety of residency, dedicated research blocks, or curricula that can be adapted to either format. [10][11][12][13][14][15] Scholarly tracks for residents have also become increasingly popular in emergency medicine (EM) residencies as a way to stimulate interest in a specific scholarly niche, marshal mentorship, and foster opportunities for scholarship. [16][17][18] Two recent systematic reviews demonstrate that no single educational intervention produces a significant increase in resident publications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include longitudinal research curricula spanning the entirety of residency, dedicated research blocks, or curricula that can be adapted to either format. [10][11][12][13][14][15] Scholarly tracks for residents have also become increasingly popular in emergency medicine (EM) residencies as a way to stimulate interest in a specific scholarly niche, marshal mentorship, and foster opportunities for scholarship. [16][17][18] Two recent systematic reviews demonstrate that no single educational intervention produces a significant increase in resident publications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous strategies for increasing resident scholarly activity exist. These include longitudinal research curricula spanning the entirety of residency, dedicated research blocks, or curricula that can be adapted to either format 10–15 . Scholarly tracks for residents have also become increasingly popular in emergency medicine (EM) residencies as a way to stimulate interest in a specific scholarly niche, marshal mentorship, and foster opportunities for scholarship 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…It is not known which is the best among the various reported methods on how to promote scholarly activities in residency programs 7,9,12–21 . Some studies concluded that “a scholarly culture is most important” to promote scholarly activities 8,16 and the JPS reform of the publication requirement policy in 2017 can be said to act at least as a compelling force, so to speak, to promote a scholarly culture.…”
Section: Discussionmentioning
confidence: 99%
“…Scholarship has become increasingly important in postgraduate medical education 1–4 . The core competencies for residents include scholarship, 1,2,5 and trainees themselves have reported a desire for and satisfaction from participation in scholarly activities 4,6–10 . However, it has been reported that scholarly activities, particularly article publication, were scarce in pediatrics residency training in Japan 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation